REACTOGENITY AND SAFETY OF ADSORBED VACCINES AGAINST DIPHTERIA, TETANUS AND PERTUSSIS (DTAP): OBSERVATIONAL MULTICENTRAL TRIAL - V.K. Tatochenko; L.S. Namazova; S.M. Kharit; O.A. Alikova; S.V. Bogidaev ("Paediatrician" Publishers LLC, 2006)
The purpose of this prospective multicenter surveillance study is evaluation of safety and reactogenicity of DTP vaccines, registered in Russia. 1424 children aged 12-20 weeks were enrolled in this study, 822 infants were vaccinated by AKDS, 411 - infanrix, 191 - tetracoc. The frequency and severity of 3 local (pain, redness and swelling) and 4 general (fever, irritability, drowsiness and loss of appetite) solicited symptoms were registered within 4 days after vaccination. The unsolicited adverse events were estimated within 30 days after vaccination, serious adverse events - during study period. The frequency of solicited adverse events was significantly low after infanrix administration than after DTPW vaccines. Infanrix also associated with less number of severe local and general reactions. Some difference in the reactogenicity profiles of AKDS and tetracoc vaccines was established. The conclusion about necessity of expanded using of DTPA in routine immunization programs was made. Key words: vaccines, reactogenicity, adverse events, surveillance study.